Determinan Persalinan dengan Metode Sectio Caesarea di Rumah Sakit Umum Daerah Kabupaten Muna - Iis Afrianty; Ika Lestari Salim; Yuniarti Eka Saputri B; Maryani Maryani (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2021)
ABSTRACT Background of Study: Delivery through a surgical process through incisions in the abdominal wall and uterine wall to give birth to a fetus is called Sectio Caesarea (SC) delivery. Methods of delivery by CS globally increased from 2000 with 12% of total births (16 million from 131.9) to 2015 to 21% of total births (29.7 million from 140.6 million). In Indonesia, according to Riskesdas in 2018, women aged 15-54 years reached 17.6% of the total number of deliveries. This shows that Indonesia has also experienced an increase in the SC number because in 2013 the SC number only reached 9.8%. Many factors that cause this SC action include premature rupture of membranes, preeclampsia, bleeding, fetal malposition, fetal distress, uterine rupture, CPD and dystocia. Objective to determine the determinants of indicators of Sectio Caesarea (SC)Methods: The type of research used in this study is quantitative. The research method is an analytic survey. in January to April 2021 with a total sample of 153. The type of data taken in this study is secondary data, namely data taken from medical records from the medical record unit.Results: Determinant indicators of caesarean section delivery, namely Chepalopelvic Disproportion (CPD) as many as 56 mothers or 36.8%, then 30 (19.7%) Premature Rupture of Membranes (PROM), Fetal dystocia 17 (14%) mothers, fetuses Macrosomia was 14 (9.2%), placenta previa was 11 (7.2%) and the last was preeclampsia/eclampsia 5 (3.3%).Conclusion: Based on the research objectives, it was concluded that the most common determinant of caesarean section delivery indicators was Chepalopelvic disproportion (CPD). Further research is needed on Maternal Body Mass Index and interpretation of fetal weight on the incidence of CPD and the long-term effects of SC Keywords: Sectio Caesarean , Determinant, CPD, Labor, Maternal Health